Hemorrhoidectomy using modern high-energy devices: advantages, disadvantages and controversial issues (review of literature) - N. A. Maistrenko; P. N. Romashchenko; A. A. Sazonov; A. G. Ardankin (Вестник хирургии имени И.И. Грекова)
A literature review of studies on the problem of providing surgical care to patients with hemorrhoids is presented. The article discusses modern approaches to the use of high-energy devices for dissection of hemorrhoids characterizes these techniques, and indicates their advantages and disadvantages. Based on the analysis of immediate and long-term results of treatment, a comparative assessment of the effectiveness and safety of hemorrhoidectomy performed using various electrosurgical instruments, plasma, laser and ultrasonic scalpels was made. It has been demonstrated that their use provides rapid hemostasis and precise tissue dissection, which leads to a decrease in the intensity of pain syndrome and the incidence of complications in the postoperative period, and also reduces the time of rehabilitation of patients. Despite the obvious positive potential of the devices presented above, their use is fraught with certain risks associated with overestimation of the hemostatic effect and, on the contrary, underestimation of the damaging effect on tissues adjacent to the dissection zone. Thus, the current level of development of biomedical technologies opens up great opportunities for improving the results of surgical treatment of patients with hemorrhoids. However, the key to their implementation is the observance of a reasonable approach to the use of certain high-energy devices, which should be based on a critical analysis of their advantages and disadvantages.